Legal Protection for the Community of Kedungputri Village, Paron Subdistrict, Ngawi Regency Against River Pollution Caused by Tofu Industry Waste - Mayang Widianti; Anik Tri Haryani; Krista Yitawati; Sarjiyati (Blantika: Multidisciplinary Journal, 2026)
This study aims to analyze the form of legal protection for communities around river areas affected by pollution caused by the tofu manufacturing industry and the factors that hinder its implementation. This study (Legal Protection For The Community of Kedungputri Village, Paron Subdistrict, Ngawi Regency Against River Pollution Caused By Tofu Industry Waste) uses a normative legal method with a statutory approach and a conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials obtained through literature study. The analysis of legal materials was conducted qualitatively using a prescriptive analytical method. The results of the study indicate that legal protection for the community can be provided through preventive and repressive measures. Preventive protection is carried out through obligations to manage waste, the provision of Wastewater Treatment Plant (WWTP) facilities, as well as supervision and guidance by the authorized regional government. Repressive protection is carried out through the application of administrative sanctions against perpetrators of pollution and the obligation to restore the environment in accordance with applicable laws and regulations. Obstacles in the implementation of legal protection include low levels of compliance by business actors with environmental regulations, limited waste treatment facilities, low public awareness, cultural factors that prioritize deliberation, and suboptimal enforcement of sanctions against environmental violations in the area.